An integrated framework for refinery scheduling and operational optimization - Siraj, K.M. (Trans Tech Publications Ltd, 2014)
This work deals with an integrated decision at the refinery scheduling and operational optimization levels. Re-scheduling is performed as a means to integrate both of these levels. Results indicate that the total benefit obtained by the proposed integrated method managed to increase 16 of the base case profit. Â© 2014 Trans Tech Publications, Switzerland.